Can avian functional traits predict cultural ecosystem services? - Alejandra Echeverri; Daniel S. Karp; Robin Naidoo; Joseph A. Tobias; Jiaying Zhao; Kai M. A. Chan (People and Nature, 2020)
Abstract The functional trait diversity of species assemblages can predict the provision of ecosystem services such as pollination and carbon sequestration, but it is unclear whether the same trait‐based framework can be applied to identify the factors that underpin cultural ecosystem services and disservices. To explore the relationship between traits and the contribution of species to cultural ecosystem services and disservices, we conducted 404 questionnaire surveys with birdwatchers and local residents in Guanacaste, Costa Rica. We used an information–theoretic approach to identify which of 20 functional traits for 199 Costa Rican bird species best predicted their cultural ecosystem service scores related to birdwatching, acoustic aesthetics, education and local identity, as well as disservices (e.g. harm to crops). We found that diet was the most important variable explaining perceptions of cultural ecosystem service and disservice providers. Aesthetic traits such as plumage colour and pattern were important in explaining birdwatching scores. We also found people have a high affinity for forest‐affiliated birds. The insight that functional traits can explain variation among cultural perspectives on values derived from birds offers a first step towards a trait‐based system for understanding the species attributes that underpin cultural ecosystem services and disservices.